Catherinum flavum - Shalaeva, Kate; Boxshall, Geoff (Zenodo, 2014)
Catherinum flavum (Hoek, 1883) Fig. 20 Scalpellum flavum Hoek, 1883: 127, pl. VI, fig. 9, pl. X, figs 7–9. Catherinium flavum : Zevina, 1981a: 253, fig. 188. Material examined. Three full-grown syntypes (two of them deteriorated) NHM UK 2013.1098–1100 and additional material (see remarks) NHM UK 2013.1101-1102, Stn 146: Indian Ocean, Antarctic and Southern (North-east of Prince Edward Island); 2515 m. Diagnosis. The only diagnosis is that of Hoek (1883), which includes description of the appendages. Distribution. Indian Ocean, Antarctic and Southern. Known depth 2515 m. Remarks. A thorough redescription of the appendages is needed. Hoek (1883) based his description on three “full-grown specimens” from Stn 146. The jar in the NHM collection contains two vials: one with two large (Fig. 20 A, B; capitulum length 8 mm) and one medium size (Fig. 20 C; capitulum length 5 mm) specimens, the other with one medium size specimen (Fig. 20 D; capitulum length 6 mm), one small specimen and some fragments. We infer that the former vial contains the three specimens mentioned by Hoek (1883). The latter vial is treated as additional material, and should not be accorded type status. Genus Pilsbryiscalpellum Zevina, 1978 Arcoscalpellum Newman & Ross 1971: 42 (part). Pilsbryiscalpellum Zevina, 1978b: 1348; Liu & Ren, 1985: 201. Diagnosis. Inframedian latus triangular, umbo basal; carinal latus umbo in carinobasal part, significantly protruding caudal appendages small, consisting of one to seven segments. Type species. Scalpellum parallelogramma Hoek, 1883. Composition. Four species. Distribution. Polar areas. Known depth range 100 to 1097 m. Genus Pilsbryiscalpellum Zevina, 1978 Arcoscalpellum Newman & Ross 1971: 42 (part). Pilsbryiscalpellum Zevina, 1978b: 1348; Liu & Ren, 1985: 201. Diagnosis. Inframedian latus triangular, umbo basal; carinal latus umbo in carinobasal part, significantly protruding caudal appendages small, consisting of one to seven segments. Type species. Scalpellum parallelogramma Hoek, 1883. Composition. Four species. Distribution. Polar areas. Known depth range 100 to 1097 m. : Published as part of Shalaeva, Kate & Boxshall, Geoff, 2014, An illustrated catalogue of the scalpellid barnacles (Crustacea: Cirripedia: Scalpellidae) collected during the HMS " Challenger " expedition and deposited in the Natural History Museum, London, pp. 1-63 in Zootaxa 3804 (1) on pages 32-33, DOI: 10.11646/zootaxa.3804.1.1, http://zenodo.org/record/4917932 : {"references": ["Hoek, P. P. C. (1883) Report on the Cirripedia collected by H. M. S. \" Challenger \" during the years 1873 - 1876. Systematic part. Report on the Scientific Results of the Voyage H. M. S. \" Challenger \", during the years 1873 - 7, Zoology, part 25 (8), 1 - 169.", "Zevina, G. B. (1981 a) Cirriped crustaceans of the suborder Lepadomorpha (Cirripedia, Thoracica) of the World Ocean. Part 1. Family Scalpellidae. Opredeliteli po Faune SSSR, Leningrad, 398 pp. [in Russian]", "Newman, W. A. & Ross A. (1971) Antarctic Cirripedia. Antarctic Research Series, 14. American Geophysical Union, Washington, 257 pp.", "Zevina, G. B. (1978 b) A new classification of the Scalpellidae (Cirripedia, Thoracica). Part 2 Subfamilies Arcoscalpellinae and Meroscalpellinae. Zoologicheskii Zhurnal, 57 (9), 1343 - 1352. [in Russian]", "Liu, R. & Ren, X. (1985) Studies on Chinese Cirripedia (Crustacea). 6. Suborder Lepadomorpha. Studia Marina Sinica, 10, 179 - 184."]}